Animal model of diabetic keratopathy - Pitra Ariesta Shinta Dewi; Ratna Sitompul; Jeanne Pawitan; Aroem Naroeni (ARSHI Veterinary Letters, 2019)
Diabetic keratopathy is one of the most common ocular complications in diabetes mellitus. Protocol for diabetes induction in rat model also has been established in many centers. Nonetheless, method in developing diabetic keratopathy rat model has not been well covered. Streptozotocin (STZ) -induced diabetes is widely being used as animal diabetic model. The purpose of this study is to obtain an animal model of diabetic keratopathy that can be used to study the morphology, metabolism, and function of cornea in cases where human samples can be difficult to obtain. A single dose STZ (50 mg/kg) was injected intraperitoneally to control and intervention group. Plasma glucose level concentrations were tested in day 3 postinjections. Obtained animal model of diabetic keratopathy, with significant difference of blood glucose level between intervention and control group (P<0.00). Sensibility of cornea was decreased by week 14th in intervention group. Epithelial defect were more prominent in diabetic group. Despite the differences between human and animal characteristic of diabetic keratopathy, the use of animal models has contributed to better understanding of this disease and to examine more effective treatment.